2018
DOI: 10.1074/jbc.m117.793281
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii disrupts β1 integrin signaling and focal adhesion formation during monocyte hypermotility

Abstract: The motility of blood monocytes is orchestrated by the activity of cell surface integrins, which translate extracellular signals into cytoskeletal changes to mediate adhesion and migration. Toxoplasma gondii is an intracellular parasite that infects migratory cells and enhances their motility, but the mechanisms underlying T. gondii-induced hypermotility are incompletely understood. We have investigated the molecular basis for the hypermotility of primary human peripheral blood monocytes and THP-1 cells infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…Impact of focal adhesion kinase (FAK) inhibition on cellular barrier integrity and transmigration of Toxoplasma gondii(a) Transcellular electrical resistance (TCER) of Caco2 and murine brain endothelial cell (MBEC) monolayers upon treatment with FAK inhibitor 12.5 μM). In contrast, challenge with MOI-equivalent or higher doses of T. gondii lysate (or LPS) did not reduce pFAK levels.This indicated an effect mediated by live intracellular tachyzoites and is well in line with recent reports of FAK dysregulation in toxoplasma-infected DCs and monocytic cells(Cook, Ueno, & Lodoen, 2018;Olafsson, Ross, Varas-Godoy, & Barragan, 2019). (b) Permeability to FITC-dextran (3 kDa) in same setup as in (a).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Impact of focal adhesion kinase (FAK) inhibition on cellular barrier integrity and transmigration of Toxoplasma gondii(a) Transcellular electrical resistance (TCER) of Caco2 and murine brain endothelial cell (MBEC) monolayers upon treatment with FAK inhibitor 12.5 μM). In contrast, challenge with MOI-equivalent or higher doses of T. gondii lysate (or LPS) did not reduce pFAK levels.This indicated an effect mediated by live intracellular tachyzoites and is well in line with recent reports of FAK dysregulation in toxoplasma-infected DCs and monocytic cells(Cook, Ueno, & Lodoen, 2018;Olafsson, Ross, Varas-Godoy, & Barragan, 2019). (b) Permeability to FITC-dextran (3 kDa) in same setup as in (a).…”
supporting
confidence: 89%
“…Although that study did not address the impact of infection on polarisation or barrier integrity, it is plausible that similar mechanisms explain the dephosphorylation of FAK upon T. gondii infection. Indeed, β1-integrin regulation and motility in toxoplasma-infected DCs and monocytes was recently linked to FAK dysregulation (Cook et al, 2018;Olafsson et al, 2019). Additionally, because redistribution of β1-integrins is observed upon T. gondii infection in DCs (Weidner et al, 2013), it is also possible that FAK dysregulation impacts on β1-integrin signalling and focal adhesion reorganisation in endothelial and epithelial cells and that the resulting increased vascular or epithelial permeability facilitates passage of T. gondii (Izawa et al, 2017).…”
Section: Reduced Phosphorylation Of Fak In Caco2 Cells and Mbecs Upmentioning
confidence: 99%
“…Somewhat perplexingly, these studies reported that infection inhibited integrin‐mediated adherence in vitro yet enhanced endothelial crawling in a manner sensitive to antibody blockade of integrin–ligand pairings (Cook et al, ; Harker et al, ). A separate study reported that T. gondii infection transiently decreases adherence of peritoneal macrophages and J774 macrophages to the integrin ligands fibronectin, laminin, and collagen IV (Ga Dama, Ribeiro‐Gomes, Guimaraes, & Arnholdt, ).…”
Section: Leukocytes As Trojan Horsesmentioning
confidence: 99%
“…Alternatively, T. gondii infection might reprogram monocyte motility to promote dissemination. This idea is suggested by a collection of in vitro studies that showed that infection alters the rolling and crawling of monocytes interacting with endothelial monolayers or fibronectin-coated substrates (Cook, Ueno, & Lodoen, 2018;Harker et al, 2013;Ueno et al, 2014).…”
Section: Leukocytes As Trojan Horsesmentioning
confidence: 99%
See 1 more Smart Citation